Educational Leadership in Nepal: Past Experiences, Present Challenges, and Future Prospects (Okhaldhunga Journal, 2026)
Leadership in the education sector plays a pivotal role in improving the quality, equity, and effectiveness of the education systems. However, in Nepal, there is still, much to do for the expansion of educational access and to increase literacy rates, and the quality of education. The study analyses perspectives on educational leadership in Nepal. It evaluates the educational situation and performance in terms of leadership, examines the leadership theories in corporations and educational frameworks on an international scale, and explores the leadership practices in the local Nepali context, specifically the rural and decentralized contexts. A qualitative, secondary-data-based research method is employed in this study. Nepal has an administrative and compliance-based educational leadership. There is a low level of instructional and distributed leadership practices, which are inconsistently used. The systems of governance in schools are neither continuous, nor clear, nor leadership-driven. Leadership training is not well institutionalized in the education system. There is underutilization of global leadership models, even though they are relevant to the Nepal context. The development of educational leadership should be officially incorporated into the national and provincial education reforms. Clear policies to institutionalize leadership preparation and lifelong learning of head teachers and local education officials motivate and give pressure for the right output. The appointment, transfer, and evaluation of teachers’ policies must focus on leadership competence, accountability, and instructional performance. Moreover, schools’ management must establish well-structured roles and responsibilities for School Management Committees and Parent-Teacher Associations to ensure transparency and continuity. The study proposes the reforms in context sensitivity and emphasizes the fact that the professionals should be constantly developed, the administrative load should be minimalized, the ethical responsibility and the system coherence must be taken into consideration, and the school leaders should enhance the quality of education.